Global Warming Impacts Micro-Phytoplankton at a Long-Term Pacific Ocean Coastal Station - Ajani, Penelope A.; Davies, Claire H.; Eriksen, Ruth S.; Richardson, Anthony J. (Frontiers in Marine Science, 2020)
Understanding impacts of global warming on phytoplankton – the foundation of marine ecosystems – is critical to predicting changes in future biodiversity, ocean productivity, and ultimately fisheries production. Using phytoplankton community abundance and environmental data that span 90 years (1931-2019) from a long-term Pacific Ocean coastal station off Sydney, Australia, we examined the response of the phytoplankton community to long-term ocean warming using the Community Temperature Index, an index of the preferred temperature of a community. With warming of 1.8℃ at the site since 1931, we found a significant increase in the community temperature index from 1931-1932 to 2009-2019, suggesting that the relative proportion of warm-water to cold-water species has increased. The Community Temperature Index also showed a clear seasonal cycle, with highest values at the end of austral summer (Feb/Mar) and lowest at the end of winter (Aug/Sept), a pattern well supported by other studies at this location. The shift in CTI was a consequence of the decline in the relative abundance of the cool-affinity (optimal temperature = 18.7℃), chain-forming diatom Asterionellopsis glacialis (40% in 1931-1932 to 13% in 2009 onwards), and a substantial increase in the warm-affinity (21.5℃), also chain-forming diatom Leptocylindrus danicus (20% in 1931-1932 to 57% in 2009 onwards). L. danicus reproduces rapidly, forms resting spores under nutrient depletion, and displays a wide thermal range. Species such as L. danicus may provide a glimpse of the functional traits necessary to be a ‘winner’ under climate change.